The climate change effect on the african monsoon region : evolution of the precipitation and atmospheric fields in the CMIP3 and CMIP5 simulations under the AIB and rcp45 scenario (1960-1999, 2031-2070) - (:unkn) unknown (My University, 2013)
The fourth IPCC report in 2007 established the synthesis of previously published work onthe effects of climate change on global and regional scales. It shows in particular that no consensuscan be found with regard to the future of rainfall — and atmospheric dynamics- associatedwith region — African monsoon. This dissertation revisits this issue in the light of new dataand using an approach avoiding over-representation of the number of simulations available forone type of model and taking into account the diversity of models and their evolution in time :twenty general circulation models (GCMs) participating in the exercises CMIP3 (twelve GCMs)and CMIP5 (eight GCMs) under the A1B emissions scenario and rcp4.5, respectively. Outputsare analyzed on two 40-year periods, — ‘Present’ (1960-1999) and ‘Future’ (2031-2070) — anddiscussed in terms of likelihood, through an approach allowing us to both quantify differences‘future’ minus ‘present’, measure robustness and statistical significances and associate a probabilitymeasuring the model consensus as a function of scales and variables.Analyzes conducted on CMIP3 and CMIP5 show that consensus on the effect of climatechange in West Africa can be achieved if we do not consider the Sahel as a whole and homogeneousentity but at lower scales. The results show contrasted responses over the centraland western Sahel, with for the future, (i) an increase in precipitation in the central regionexplained primarily by a greater convergence of flow in the lower layers and a most northerlymonsoon penetration over the continent, (ii) a rainfall decrease in the western Sahel explainedby increased Walker-type circulation, African easterly jet and mid-level subsidence. Moreover,we can expect a change in the mean annual cycle of the monsoon season with a delayed withdrawallinked to additional inputs of moisture from the Atlantic due to increasing thermal andmoisture contrasts between ocean and continent but
Keywords: African Research